KONSEKUENSI MANAJEMEN LABA, TATA KELOLA DAN TANGGUNGJAWAB SOSIAL TERHADAP REPUTASI PERUSAHAAN - Susi Retna Cahyaningtias; Wahidatul Husnaini; Elin Erlina Sasanti; Lukman Effendy; Robith Hudaya (Jurnal Riset Akuntansi, 2017)
The objective of this study is to examine the earnings management consequences, good corporate governance, and corporate social responsibility toward company reputation. Research population is manufacturing companies listed in Indonesia Stock Exchange during 2013-2014. Pursuant to purposive sampling method, the study obtained 31 companies as sample of the study since not many companies have reputation data. The result of the study found that only good corporate governance improves the company’s reputation, while earnings management consequences and corporate social responsibility were found to have no influence on company reputation.